Peculiarities of course fixing system control for mode of precise setting in horizon - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2004)
Some kinematical schemes of course fixing systems are analysed. Peculiarities of course fixing system control for mode of precise setting in horizon are considered. Relationships for control and correction moments are suggested.